Argumentation in Pragmatics (2014–2024): A Linguistic Perspective on Themes and Impact - Tursunova, Munisa; Kushiyeva, Nodira; Usarova, Dildora; Tursunova, Dilfuza; Gulsara, Kurbonova; Axmedov, Oybek (Forum for Linguistic Studies, 2025)
The evaluation of research is of considerable importance in identifying the evolution and the potential direction of subsequent research. We conducted a bibliometric analysis of 262 studies published between 2014 and 2024, accessed through the Web of Science database. A visual representation of our performance analysis was generated using the VOS viewer program, and a scientific map was developed to illustrate the relationships between the bibliometric data elements. This study examined research trends in argumentation in pragmatics, focusing on the leading journals, keywords, and highly cited publications. The study aimed to provide a consolidated understanding of existing pedagogical research on teaching argumentation, including publications that have shaped the field. In particular, the study would draw attention to the key contributors and most significant identified works to influence future research and add to the development of effective pedagogical approaches to argumentation literacy. These findings would make a valuable contribution to educators and researchers interested in research studies and help advance the specialized knowledge of language instruction, and become more inclusive with research to contribute to advancing knowledge. It remains important for educators and researchers to try to disseminate the findings from their research and reach out to colleagues from across institutions and countries to ensure that their findings reach a larger audience. The bibliometric review has provided two pedagogical categories that are most effective in teaching argumentation: task-based argumentation pedagogy and AI technology-enhanced teaching. The review introduces the TAP-5 taxonomy of methodological strands and PACER, a five-stage integrative cycle, as its theoretical contribution to facilitating the organization and further development of research on teaching argumentation in pragmatics. These findings would add value and conclusions for educators and researchers interested in exploring the teaching of argumentation in other parts of the world.